The Effectiveness of Cooperative Integrated Reading and Composition Model in the Teaching and Learning Narrative Essay Writing - Wahyu Ningsih; Nur Khadijah Razak (Journal of Indonesian Language Education and Literary, 2017)
activity is the most essential activity in human life. This is true, because communicating is not just about delivering and receiving information, but also expression, asking for responses and responding with all the complexities of language that are not always realized by everyone. Bahasa Indonesia as a means to think logically, analytically, creatively, and systematically makes one can easily make new innovations in everyday life especially in education. The 1945 Constitution explains Indonesia's position as a language of unity is very strong. Article 36 reads, "The language of the country is the Indonesian language". The broader translation of this article can mean that the use of the Indonesian language is an obligation for every state interest and governance matters. Consequently, conservation efforts, fostering, and developing the Indonesian language are the responsibility of every citizen. The importance of fostering and developing Indonesian language is taught in all levels of education, from elementary, secondary, to college. Indonesian language learning can not be separated from learning to read, write, listen, and speak. Humans can acquire the skills of speaking and listening naturally, because both are normal human nature. While the skills of writing and reading can only be obtained through exercises and with mastery of certain concepts. Writing skills is a demand for everyone to master, especially for those who move or live in the academic world. Writing skill is one of the subjects taught to the students of Indonesian Language and Literature Studies Program at Muhammadiyah University of Makassar. Discourse can be used as a means to train students' writing skills. Selection of learning model is also very important to elicit enthusiastic students when following the lecture. The Cooperative Integrated Reading and Composition model is a model that includes reading and writing skills. The application of the model is expected to help students in pouring the idea that the text is not only read in their own circles but also can be published to be enjoyed by the general public.